2018
DOI: 10.3390/beverages4040092
|View full text |Cite
|
Sign up to set email alerts
|

The German Wine Market: A Comprehensive Strategic and Economic Analysis

Abstract: Even though it is famous for beer, Germany offers one of the most attractive wine markets, exemplified by being the fourth biggest wine consumption market and a world champion in sparkling wine consumption as well as in wine imports. Still, fragmentation, intensive competition, lack of growth, and a changing environment speak to a challenging market for suppliers. In the absence of a comprehensive investigation on the market, this article aspires to deliver an economic and strategic market analysis. The statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…The people began to view wine as a daily drink, and became increasingly curious about higher quality wines (Corsi et al, 2013), which generated an increase in sparkling wine consumption, especially among women (Rod and Beal, 2014). Germany, despite presenting a constant fall, starting with 11.5 points in 2004 and experiencing fluctuations between 2006 and 2011, continued to be a strong importer, due to having sparkling wine as an occasional celebratory beverage (Dressler, 2018). According to Szolnoki and Hoffmann (2014), it was one of the few countries in the world that had very diversified structured distribution channels, offering a wide variety of purchase points for the German sparkling wine consumer.…”
Section: Market Share and Concentration Of Importsmentioning
confidence: 99%
“…The people began to view wine as a daily drink, and became increasingly curious about higher quality wines (Corsi et al, 2013), which generated an increase in sparkling wine consumption, especially among women (Rod and Beal, 2014). Germany, despite presenting a constant fall, starting with 11.5 points in 2004 and experiencing fluctuations between 2006 and 2011, continued to be a strong importer, due to having sparkling wine as an occasional celebratory beverage (Dressler, 2018). According to Szolnoki and Hoffmann (2014), it was one of the few countries in the world that had very diversified structured distribution channels, offering a wide variety of purchase points for the German sparkling wine consumer.…”
Section: Market Share and Concentration Of Importsmentioning
confidence: 99%
“…Currently it can also be purchased online. As stated by (Dressler, 2018), online offers for wine are increasing as the general consumer attitude to buy online increases. (Quinton and Harridge-March 2008) analyzed a sample of store and online wine buyers and found that it is relevant that the online service instills trust for the first-time buyer.…”
Section: The Wine Industry and E-commercementioning
confidence: 99%
“…The Australian market is almost 90% supplied by domestic production, with a growing dominance of supermarket distribution and increased relevance of online sales [29]. Contrary to Australia, France, and Italy, which are big wine exporters, in Germany imports represent almost 50% of the domestic wine consumption, and sales are 85% off-premise and 15% on-premise [19].…”
Section: Datamentioning
confidence: 99%